Game Edukasi Mengenal Huruf Katakana dan Hiragana Berbasis Android - Adi Prayoga, Agus Gede; Bayupati, I Putu Agung; Wiranatha, A.A.K. Agung Cahyawan (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 6, No.3 Desember 2015, 2015)
Japanese language is different from other language in general, because in its writing is using Katakana and Hiragana letter. The use of Japanese is in various need, especially in communication for example entertaining tourists. Japanese language learning in Indonesia facing several problems among other are lack of infrastructure in practicing and also boring atmosphere which make students having difficulty in learning. Educational game application for mobile device is a new learning method is considered as a tool to attract one’s interest to learn. Educational Games to Indentify Katakana and Hiragana Letter is created in order to help to overcome the difficulty in learning Japanese Language relate to mastery Katakana and Hiragana letter. Learning material which is implied in the game came from Ni Hon Go 1 and Ni Hon Go No Kyoukasho curriculum. Game have three learning features such as table, letter writing and guessing, there are also entertaining addition features. Based on questionnaire data result on 30 students having difficulty in learning Japanese language, as much as 60% of respondents say that the game was easily understood as a Japanese language learning media.